Efficacy of Lecture cum demonstration versus video-based teaching regarding active management of third stage of labor in terms of knowledge and skills of GNM students: An interventional study - Deepshikha David; Simarjeet Kaur; Adiba Siddiqui; Jyoti Sarin (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Educational interventions have been associated with improved performance and significant changes, especially in perinatal outcomes. Teaching is one of the main components in educational planning which is a key factor in conducting educational plans through various teaching strategies such as simulation, demonstration and video teaching. AIM: The study aimed to assess lecture cum demonstration (LCD) versus video-based teaching (VBT) regarding active management of the third stage of labor (AMTSL) in terms of knowledge and skills of General Nursing Midwifery (GNM) students. METHODS: This was a quasi-experimental study conducted on 100 GNM third-year students selected by purposive sampling and randomly assigned to LCD (n = 50) and VBT (n = 50) groups. Sample characteristics performa, Structured Knowledge Questionnaire, and observational checklist were used to collect data from GNM students through self-report and observational technique. RESULTS: The study results showed that the mean posttest knowledge scores of LCD (17.32 ± 2.14) and VBT group (16.90 ± 2.41) were nearly equal and mean rank posttest skills score of LCD group (54.40) was slightly higher than VBT group (49.51), but computed " t " value of mean posttest knowledge and computed " Z " value of skill score of both LCD and VBT group (0.47, 0.54) were found to be statistically non-significant at 0.05 level of significance. CONCLUSION: It can be concluded that both LCD and VBT were found to be effective in improving knowledge and skills of GNM students regarding AMTSL.